2022
DOI: 10.3389/fonc.2022.844214
|View full text |Cite|
|
Sign up to set email alerts
|

Agonists Specific for κ-Opioid Receptor Induces Apoptosis of HCC Cells Through Enhanced Endoplasmic Reticulum Stress

Abstract: Cancer pain is an important factor affecting life quality of patients especially in the advanced stage and relieving pain is one of fundamental strategies for cancer treatment. Opioids such as morphine are the most widely used in clinics. However, they have been reported to be associated with the occurrence and development of several types of cancer. Thus, search for an opioid that has analgesic effect and can retard cancer progress simultaneously is critical for cancer management. In this study, we first exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“… 38 Evidence indicates that MOR activation can decrease ER stress and protect cells from excitotoxicity-induced apoptosis, 35 whereas KOR activation induces apoptosis through the enhanced ER stress pathway. 49 BPN can exert its effects through activation of MORs and inhibition of KORs, leading to decreased cell death. In addition, BPN significantly increased XPB1s at 7 days post-injury in both male and female TBI + BPN mice, compared to sham and TBI + saline mice.…”
Section: Discussionmentioning
confidence: 99%
“… 38 Evidence indicates that MOR activation can decrease ER stress and protect cells from excitotoxicity-induced apoptosis, 35 whereas KOR activation induces apoptosis through the enhanced ER stress pathway. 49 BPN can exert its effects through activation of MORs and inhibition of KORs, leading to decreased cell death. In addition, BPN significantly increased XPB1s at 7 days post-injury in both male and female TBI + BPN mice, compared to sham and TBI + saline mice.…”
Section: Discussionmentioning
confidence: 99%
“…ERS can affect the progression of lung adenocarcinoma by participating in immune-related biological processes such as T-cell failure and lymphocyte differentiation [13]. ERS promotes apoptosis of hepatocellular carcinoma cells by upregulating the Perk pathway [14]. In addition, many studies have shown that the occurrence and development of CRC are related to ERS.…”
Section: Introductionmentioning
confidence: 99%